Analisis Yuridis Terhadap Pertanggungjawaban Organ Yayasan Untuk Mewujudkan Kepastian Hukum (Studi Penelitian di Yayasan Hati Senang Abadi Berkedudukan di Kota Tanjungpinang) - Sovia, Sovia; Respationo, Soerya; Erniyanti, Erniyanti; Tartib, Muhammad (UNES Law Review, 2023)
The purpose of this research is to determine legal regulations, implementation and factors that become obstacles and solutions to the accountability of foundation organs to realize legal certainty at the Hati Senang Abadi Foundation. The data collection technique used is through literature study and interviews. Data processing is carried out using qualitative methods and classified aspects of certain problems and explained in effective sentences. The results of this research show that the legal accountability arrangements for foundation organs are regulated in the Foundation Law and the Articles of Association of each foundation. Based on the data collection and data analysis process, it is known that the organs of the Hati Senang Abadi Foundation carry out good management. Foundation organ already done their job well but still need some advice, education and executive board soberity to run and maximalize role and obligations in running the foundation